Questions for more insightful and useful analyses of barriers and facilitators to public involvement and engagement in health research: a critical narrative review - Lauge Neimann Skov (Research Involvement and Engagement, 2026)
Abstract Background Public involvement and engagement in health research is widely promoted yet remains challenging and unevenly practised across health research contexts. To explain this, it has become popular to analyse so-called barriers to and facilitators of involvement. However, critics argue that such analyses are simplistic and generate little knowledge to guide action. This review critically appraises the typical form of barrier analysis concerned with public involvement in health research and proposes eight lines of inquiry that may make future analyses more insightful and useful. Methods This is a critical narrative review informed by a systematic search of four health research databases in June 2026. Records were eligible if they stated a research objective concerning barriers to public involvement in health research and reported their findings in a topical manner, meaning that they mainly named and summarised findings and organised them in themes. These topical barrier analyses were critically appraised in relation to their capacity to improve understanding and inform involvement practice, and their findings were contrasted with broader debates about public involvement. Findings Eighty topical barrier analyses concerning public involvement in health research were identified and reviewed. The review argues that the analyses pay little attention to what a barrier is or means, what it obstructs, when and where it arises, and whom it affects. Their recommendations are abstract, basic or largely aspirational; they link irregularly to the barriers identified; and they are usually directed towards researchers while doing little to help members of the public. The review argues that these shortcomings stem from a focus on two repetitive questions: what are the barriers, and how might they be overcome? To move beyond the analytical shortcomings, the review proposes eight new lines of inquiry: five aimed at making analyses more insightful and three at making them more useful. Conclusion Unlike critics who call for barrier analyses to be abandoned, or those who call for methodological refinements, this review argues that the future of barrier analyses depends on a willingness to ask new questions that may generate knowledge that is more insightful and useful than what is already known.